Lactic acid production from lactose by Lactobacillus plantarum: kinetic model and effects of pH, substrate, and oxygen - Fu, W.; Mathews, A.P.
Batch fermentation of lactose to lactic acid was conducted using Lactobacillus plantarum under aerobic and anaerobic conditions (operation without aeration). Synthetic lactose medium was used as the culture medium and the effects of pH and substrate concentration on cell growth and lactic acid production were investigated. Lactic acid fermentation with this bacterium is found to be homolactic and primarily growth associated. Optimum pH for cell growth and acid production was found to be between 5 and 6. Anaerobic fermentation gave a higher lactic acid yield of about 2.3 times that for aerobic fermentation. Cell growth rate was about two times higher, but cell yield was only about 80
Keywords: LACTOSE; LACTIC ACID; WHEY; FERMENTATION; LACTOBACILLUS PLANTARUM; KINETIC MODEL